OBSTETRICS ILLUSTRATED - Hanretty, Kevin P. (Churchill Livingstone/Elsevier, 2010)
This popular guide uses illustrations and concise, integrated text to describe the essentials of obstetric practice today. From the physiology of reproduction through antenatal care and disorders in pregnancy to labour and the puerperium period, readers will find an easy-to-grasp presentation of the field's most important issues.